Pengaruh Pengaruh Penggunaan Metode Glenn Doman Terhadap Kemampuan Literasi Anak Usia 5-6 Tahun di TK Islam Al-Izhar Cendekia Makassar: Pengaruh Penggunaan Metode Glenn Doman Terhadap Kemampuan Literasi Anak Usia 5-6 Tahun di TK Islam Al-Izhar Cendekia Makassar - Rahmah, Auliya; Musi, Muhammad Akil; Muharram, Muharram; Herlina, Herlina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This research aims to determine: (1) The description of the implementation of the Glenn Doman method in 5-6-year-old children (2) The description of the literacy skills of 5-6-year-old children before and after the implementation of the Glenn Doman method (3) The effect of the implementation of the Glenn Doman method on literacy skills of 5-6-year-old children. This research is a quantitative study with an experimental method, a pretest-posttest Nonequivalent Control Group Design research design. The subjects in this study were 22 children, divided into two groups, namely 11 children in the experimental group and 11 children in the control group. Data collection techniques used tests and observations with the help of observation guidelines for children's literacy skills. Data analysis used descriptive statistical analysis and non-parametric statistics. The results of this study indicate that (1) The Glenn Doman method can stimulate children's literacy skills (2) There is a significant difference in children's literacy scores before and after being given treatment, based on the results of the Wilcoxon test for the experimental group, the calculated Z value is -2.943 and the significance value is 0.003. (3) There is an effect of using the Glenn Doman method on children's literacy skills.